Food Crop Land Allocation: Integrating Land Suitability Analysis and Spatial Forestry, Study Case Katingan, Indonesia - Ramdhani; Widiatmaka; Trisasongko, Bambang Hendro (Institut Pertanian Bogor (IPB University), 2023)
The Indonesian government strives to expand agricultural lands, primarily beyond Java, through food estate programs. However, there has been a strong likelihood that this endeavor might intersect with forests and forest designation areas. This study aims to determine land suitability and its potential allocation for food crops at the interface of forestry and agriculture in Katingan District. Paddy (Oryza sativa L) and sorghum (Sorghum bicolor L) were selected as the crop species being analyzed, employing a coupling of the analytical hierarchy process and GIS. Forest area designation and land cover maps were incorporated into land allocation scenarios. The results showed that there were 74.254 ha in the